Self-efficacy and implementation intentions in home rehabilitation of stroke patients: the parallel mediating role of recurrence risk perception and outcome expectations - Jiang, Xiaowen; Sun, Qiuxue; Tang, Rong; Liu, Shuxian; Chen, Xi; Lv, Yumei (Frontiers in Psychology, 2025)
BackgroundSelf-efficacy can improve the implementation intentions level of rehabilitation exercise in stroke patients. Yet, the underlying mechanism of benefits remains unclear especially in the home-based environment.ObjectiveThis study aims to assess the level of implementation intentions in home-based rehabilitation exercises among stroke patients, clarify the relationship between self-efficacy and implementation intention, and determine whether recurrence risk perception and outcome expectations mediate this relationship.MethodsWe conducted a quantitative cross-sectional study, recruiting 216 stroke patients who met the inclusion and exclusion criteria from three communities in Daqing City between June 2024 and April 2025. The mediating effects of recurrence risk perception and outcome expectations were assessed using Model 4 (parallel mediation) of the SPSS PROCESS macro with the bootstrap method.ResultsThe results showed that the score of home rehabilitation exercise implementation intentions of stroke patients was 60.62 ± 6.87, which still needs to be improved. Mediation analysis showed that self-efficacy played a significant direct role in executive intention, and recurrence risk perception and outcome expectations mediated the relationship between self-efficacy and the implementation intentions.ConclusionThere is considerable room for improvement in the implementation intentions of home rehabilitation exercise in stroke patients. This can be enhanced by intervening in rehabilitation self-efficacy, which in turn can influence recurrence risk perception and outcome expectations to improve the level of implementation intentions.ImpactThis study aims to draw the attention of healthcare providers and family members to patients’ self-efficacy, recurrence risk perception, and outcome expectations, and advocate that the above variables can be used as the focus of future intervention in patients ‘home rehabilitation exercise implementation intentions.